SISTEM INFORMASI PEMBAYARAN SPP PADA SMA KATOLIK 1 KABANJAHE - Br. Tarigan, Santa Lidwyna; Simarmata, Emma Rosinta; Aritonang, Mendarisan (Universitas Methodist Indonesia, 2022)
SMA Katolik 1 Kabanjahe School is an educational institution under the leadership of YPK Don Bosco KAM that always improves the quality of education services. Like education to find out the SPP payment information service. Efficient, fast, accurate, and secure tuition payment is needed for the administration of the school. For this, we need a system that requires SPP payment processes. At present, the administrative registration process in SMA Katolik 1 Kabanjahe School still uses a manual system and uses Microsoft Exel to process student transaction data. The problem that arises is the number of times the recording process causes a process that requires a long time making financial statements received less effective. The purpose of this research is to build an information system that will help the SPP payment process so that it reduces problems in making reports on cash receipts for the receipt of SPP payments. SPP Payment Information System Application in SMA Katolik 1 Kabanjahe School was designed with several stages consisting of data and information, needs analysis, and system design. The research method uses the waterfall method while the data collection method uses interviews, observation, and literature study. The design of this information system is created using the Visual Basaic.Net application and uses MySQL as its database.